Long noncoding RNA ANRIL protects cardiomyocytes against hypoxia/reoxygenation injury by sponging miR-195-5p and upregulating Bcl-2. Issue 61 (4th November 2019) - Zhao, Hui; Meng, Li; Xu, Chengyang; Lin, Bin; Zheng, Xiangming; Wang, Jiaxiang; Feng, Deguang
Abstract : Long noncoding RNAs have been widely accepted to play important roles in acute myocardial infarction (AMI). Abstract : Long noncoding RNAs have been widely accepted to play important roles in acute myocardial infarction (AMI). The dysregulation of cyclin-dependent kinase inhibitor 2B antisense RNA 1 (ANRIL) was discovered in AMI patients. Nevertheless, the detailed role and molecular mechanisms of ANRIL in AMI remain indistinct. The levels of ANRIL, miR-195-5p and Bcl-2 mRNA were determined by qRT-PCR. western blot was performed to assess the expression of Bcl-2, Bax, Cyclin D1 and p21. Cell proliferation was detected by CCK-8 assay, and cell apoptosis was measured by flow cytometry. The targeted correlation between ANRIL and miR-195-5p was confirmed by the dual-luciferase reporter and RNA pull-down assays. Our data revealed that ANRIL was downregulated and miR-195-5p was upregulated in the serum of AMI patients and hypoxia/reoxygenation (H/R)-induced myocardial cells. ANRIL upregulation or miR-195-5p knockdown alleviated H/R-induced myocardial cell injury. Moreover, ANRIL sequestered miR-195-5p by acting as a sponge of miR-195-5p. ANRIL upregulated Bcl-2 expression by sponging miR-195-5p. Additionally, ANRIL overexpression alleviated H/R-induced myocardial cell injury by upregulating Bcl-2. In conclusion, our study indicated that ANRIL upregulation alleviated H/R-induced myocardial cell injury partially through sponging miR-195-5p and upregulating Bcl-2, highlighting its role as a promising mediator for new therapies for AMI treatment.